Constrangimentos domésticos à política externa comercial dos Estados Unidos no Governo Clinton (1993-2001) - Cezar, Rodrigo Fagundes (2015)
This dissertation analyzes the domestic constraints that arose during the formulation and voting of US trade policy throughout Bill Clinton s administration (1993-2001) and the manner in which the Executive adjusted to these obstacles. An analytical narrative is undertaken with emphasis on: 1) the approval of NAFTA (1993); 2) the constraints to the renewal of fast-track authority (1997); 3) trade relations with China (1993-1996) and with Japan (1993-1995), 4) the normalization of trade relations with China and the WTO ministerial conference in Seattle (1999-2000). The analytic framework contains elements of different approaches such as decision units approach and bureaucratic politics model, based on the assumption that decision is made through coalitions. We argue that the way trade policy was formulated was essential for the results achieved and that the constraints were the result of divisions in the Congress, society and Executive and the difficulties related to the coordination of these actors. We conclude that the analysis provided allows us to understand more clearly the domestic constraints to the US trade policy and the manner in which the Executive adjusted to these obstacles by considering the relationship among the main actors within the decision-making process